Model Kooperatif Tipe Pair Check Berbantuan Media Tiga Dimensi untuk Meningkatkan Hasil Belajar Matematika Peserta Didik - Septiadi, Hadi; Kartini, Kartini; Rustanuarsi, Ressy (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2025)
This study aims to improve the learning outcomes of mathematics on the material of three-dimensional shapes (rectangular prism and cube) of VD class students at SDN 34 Pontianak Kota through the implementation of cooperative learning model type Pair Check assisted by three-dimensional media. The subjects of this study were 30 students of class VD in the 2023/2024 school year. This research is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. Data were collected through observation, test, and documentation techniques, then analyzed qualitatively and quantitatively. The results showed that: (1) The learning outcomes of students in cycle I reached a completeness of 67% with an average score of 76, while in cycle II the completeness increased to 90% with an average score of 85; (2) There was an increase in learning completeness by 23% and an increase in the average score by 9 points from cycle I to cycle II. Thus, it can be concluded that the implementation of the Pair Check cooperative learning model assisted by three-dimensional media can enhance the mathematics learning outcomes of fifth-grade students in the topic of three-dimensional shapes (rectangular prism and cube).